The role of the optical coherence tomography angiography in diseases of the posterior segment of the eye - Vasilijevic, Jelena; Pantelic, Jelica; Kalezic, Tanja; Avram, Nada; Dacic Krnjaja, Bojana; Popovic, Andjela; Vasovic, Dolika; Kovacevic, Igor (Medical Research, 2026)
Optical coherence tomography angiography (OCTA) is a noninvasive, quantitative tool for imaging the retina and choroid, capable of visualizing the microvasculature in three dimensions. It is widely used for diagnosing and monitoring treatment response for various diseases of anterior and posterior segment of the eye. A systematic search of the relevant literature was conducted emphasizing a period of the most intensive development and clinical application of OCT angiography. This paper aims to summarize current knowledge regarding the applications of OCTA in the diagnosis and monitoring of posterior segment retinal pathologies, and to discuss its advantages over traditional imaging techniques.
Keywords: optical coherence tomography angiography, posterior segment diseases, retinal vasculature, retinal vascular diseases